2002
DOI: 10.1038/ng825
|View full text |Cite
|
Sign up to set email alerts
|

Parameters for reliable results in genetic association studies in common disease

Abstract: It is increasingly apparent that the identification of true genetic associations in common multifactorial disease will require studies comprising thousands rather than the hundreds of individuals employed to date. Using 2,873 families, we were unable to confirm a recently published association of the interleukin 12B gene in 422 type I diabetic families. These results emphasize the need for large datasets, small P values and independent replication if results are to be reliable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
126
2
3

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(144 citation statements)
references
References 10 publications
13
126
2
3
Order By: Relevance
“…The relatively small sample size in combination with the rare frequency of the variant allele may not have been powerful enough to detect such an association. As was recently shown for IDDM, 18,24 large-scale family-based linkage studies are necessary to establish the role of the IL-12 genes in the susceptibility to CD. These efforts are currently underway.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively small sample size in combination with the rare frequency of the variant allele may not have been powerful enough to detect such an association. As was recently shown for IDDM, 18,24 large-scale family-based linkage studies are necessary to establish the role of the IL-12 genes in the susceptibility to CD. These efforts are currently underway.…”
Section: Discussionmentioning
confidence: 99%
“…Even with a plausible biological rationale for the candidacy of a gene such as IL4RA, P values in the order of 10 À5 are desirable to ensure a relatively low falsepositive rate for disease association studies and Po10 À7 -10 À8 for genome-wide association studies. [34][35][36] Obviously, a second independent even larger data set will need to be genotyped for this SNP to test if the T allele of the -3223 C4T SNP does indeed protect from T1D. New collections of families (http://www.t1dgc.org) and case-controls are under way (http://www.childhooddiabetes.org.uk).…”
Section: Discussionmentioning
confidence: 99%
“…152 In a recent comprehensive review of over 600 positive case-control studies, only six positive associations were found to have been consistently replicated. 153 A follow-up meta-analysis of a selection of the positive associations by the same authors found that eight of 25 associations were statistically significant.…”
Section: Disease Associations-conclusionmentioning
confidence: 99%